Valorization of selenium-enriched sludge and duckweed generated from wastewater as micronutrient biofertilizer. (October 2021) - Li, Jun; Otero-Gonzalez, Lila; Parao, Amelia; Tack, Pieter; Folens, Karel; Ferrer, Ivet; Lens, Piet N.L.; Du Laing, Gijs
Abstract: Selenium (Se) is an essential trace element for humans and animals with a narrow window between deficiency and toxicity levels. Application of conventional chemical Se fertilizers to increase the Se content of crops in Se deficient areas could result in environmental contamination due to the fast leaching of inorganic Se. Slow-release Se-enriched biofertilizers produced from wastewater treatment may therefore be beneficial. In this study, the potential of Se-enriched biomaterials (sludge and duckweed) as slow-release Se biofertilizers was evaluated through pot experiments with and without planted green beans ( Phaseolus vulgaris ). The Se concentration in the bean tissues was 1.1–3.1 times higher when soils were amended with Se-enriched sludge as compared to Se-enriched duckweed. The results proved that the Se released from Se-enriched biomaterials was efficiently transformed to health-beneficial selenoamino acids (e.g., Se-methionine, 76–89%) after being taken up by beans. The Se-enriched sludge, containing mainly elemental Se, is considered as the preferred slow-release Se biofertilizer and an effective Se source to produce Se-enriched crops for Se-deficient populations, as shown by the higher Se bioavailability and lower organic carbon content. This study could offer a theoretical reference to choose an environmental-friendly and sustainable alternative to conventional mineral Se fertilizers for biofortification, avoiding the problem of Se losses by leaching from chemical Se fertilizers while recovering resources from wastewater. This could contribute to the driver for a future circular economy. Graphical abstract: Image 1 Highlights: Se-enriched duckweed and sludge generated from wastewater as Se biofertilizers was valorized. Se-enriched sludge was more bioavailable than duckweed to increase Se content in beans. Se-enriched sludge is considered as the preferred slow-release Se biofertilizer.